2017
DOI: 10.1007/s00253-017-8312-7
|View full text |Cite
|
Sign up to set email alerts
|

Different fermentation processes produced variants of an anti-CD52 monoclonal antibody that have divergent in vitro and in vivo characteristics

Abstract: The anti-CD52 antibody has already been approved for the treatment of patients with resistant chronic lymphocytic leukemia, relapsing-remitting multiple sclerosis, and has demonstrable efficacy against stem cell transplantation rejection. A CHO cell line expressing a humanized anti-CD52 monoclonal antibody (mAb-TH) was cultivated in both fed-batch and perfusion modes, and then purified. The critical quality attributes of these mAb variants were characterized and the pharmacokinetics (PK) properties were invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 30 publications
0
14
1
Order By: Relevance
“…Despite the two markers are often used for describing best cell performance, the focus of critical parameters is shifted toward increased product quality . Thereby, critical quality attributes have to be defined for each molecule of interest individually and quality characteristics are predominantly defined by the process operation mode/conditions and harvest time …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the two markers are often used for describing best cell performance, the focus of critical parameters is shifted toward increased product quality . Thereby, critical quality attributes have to be defined for each molecule of interest individually and quality characteristics are predominantly defined by the process operation mode/conditions and harvest time …”
Section: Resultsmentioning
confidence: 99%
“…[24][25][26] Thereby, critical quality attributes have to be defined for each molecule of interest individually and quality characteristics are predominantly defined by the process operation mode/conditions and harvest time. 22,[27][28][29][30][31][32][33] In semicontinuous small-scale models, N-glycosylation and charge profiles changed distinctly along different culture harvest times, but not by the addition of the CB1 and CB3 feed supplements (Figure 5d, e). The variation of product quality attributes was higher between different harvest times than between different media.…”
Section: Verification Of Performance By Semicontinuous Small-scale mentioning
confidence: 99%
“…Recently, use of perfusion mode in biomanufacturing has been adopted due to the higher cell density and volumetric productivity achieved (Bonham‐Carter & Shevitz, ). Reports in the literature conducting a side‐by‐side comparison have typically shown equal or lower levels of acidic charge variants (Seo et al, ; Xu, Gavin, Jiang, & Chen, ; Zhuang et al, ) and generally more homogenous PQAs in perfusion mode (Karst, Scibona, et al, ; Karst, Steinebach, Soos, & Morbidelli, ; Steinebach et al, ). These improvements have typically been associated with better control of the culture environment through the removal of metabolic waste such as ammonia, shorter residence time in the bioreactor, and more stable operation at steady state.…”
Section: Upstream Process Strategies For Charge Variants Controlmentioning
confidence: 99%
“…In a separate publication, we noted comparable IgG glycoform patterns between our perfusion cell culture process at steady state and the fed-batch cultivation beyond the stationary growth phase [15]. In the literature, past studies produced contradictory conclusions on the IgG glycosylation when comparing the two cell culture modes, where some studies demonstrated similarities [9,10] and others showed discrepancies in the IgG glycan structures [13,14]. A recent report of a head-to-head comparison between perfusion and fed-batch cell cultures noted a strong similarity in the IgG glycosylation dynamics [45], an observation that aligns well with the result of our analysis.…”
Section: Discussionmentioning
confidence: 55%
“…Whether or not product qualities and their key controlling parameters can be directly translated from the traditional batch/fed-batch cell cultures to the perfusion cell cultivations is still unresolved. Past work on converting mAb production from batch/fed-batch to perfusion cell cultures gave conflicting reports on product qualities, where a few studies demonstrated consistent product qualities [9,10], and many others showed differences between the two production modes [11][12][13][14][15].Among the key critical quality attributes (CQAs) of therapeutic mAbs is the glycan structures of the Fc domain [16]. The N-linked glycosylation is a common post-translational modification of proteins, a process that occurs in the endoplasmic reticulum (ER) and Golgi apparatuses.…”
mentioning
confidence: 99%